The dangerous role of politics in modern millennial movements - De Villiers, Pieter G. R. (HTS teologiese studies, 2019)
This article investigates the political nature and involvement of millennialism as a religious phenomenon. It, firstly, offers a brief analysis of how millennialism shifted from a significant, but marginal role player in the history of Christianity to become part of the mainstream religious discourse in recent times. It then seeks to explain how this came about by analysing the way this development continues and resonates with the political language and thought of the 19th-century religious discourse in the United States and in early modern England since the 16th century. It finally investigates the dangerous consequences of politicising eschatology by specifically analysing the role of Israel in millennial expectations.